Agrivoltaic panel shading influences soil nutrient dynamics and microbial community structure in a wheat-cultivated field - Claudia Chiodi; Federico Gavinelli; Shunlei Li; Massimo Cagnin; Davide Del Todesco Frisone; Sara Remelli; Aldo Dal Prà; Giuseppe Concheri; Andrea Squartini; Asia Paone; Cristina Menta; Piergiorgio Stevanato (PLoS ONE, 2026)
Agrivoltaic systems (AV), which combine photovoltaic panels with crop cultivation, represent a dual land use strategy to address food and energy security challenges under growing population pressures. However, the effects of AV systems on soil biogeochemical processes and microbial communities remain insufficiently characterized. This study investigated the effects of AV trackers with varying Ground Coverage Ratio (GCR) on soil physicochemical properties, and microbial community composition and diversity at two time points (T1 and T2). Field experiments were conducted in a wheat-cultivated field using two AV configurations: standard (STV1, GCR = 13%) and extended (STV2, GCR = 41%) trackers, compared to a full-sun control (CI). Soil chemical analysis performed using a combustion analyzer showed that organic carbon, total nitrogen, Olsen phosphorus, and exchangeable calcium, potassium, and magnesium were all increased under STV2 compared to both STV1 and the control; this overall enrichment was further confirmed by ICP-OES-based elemental profiling. Amplicon sequencing of the 16S rRNA and ITS1 regions revealed reduced bacterial and fungal diversity under STV2. Significant taxonomic shifts in bacterial and fungal communities were also observed at both phylum and genus levels relative to the control. These findings suggest that extended shading from STV2 altered soil chemical properties while restructuring microbial communities, reducing diversity and favoring copiotrophic taxa, especially at T1. Overall, the results underscore the central role of agrivoltaic design, specifically shading intensity and GCR, in shaping belowground processes with relevant implications for soil health and the agroecological performance of dual land use energy–food systems.